2020
DOI: 10.21203/rs.3.rs-61952/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“INSIDE” Project on Sexual Health in Spain: The Impact of the Lockdown Caused by COVID-19

Abstract: Introduction. The COVID-19 pandemic is becoming a major hazard to public health worldwide. This is causing a significant impact on life and physical health, as well as on the psychological well-being of the general population. Since the emotional distress and the social restrictions caused by this epidemic, it must be expected that its impact will also extend to sexual health. The purpose of this study, the first including a large sample of the Spanish general population, was to analyze sexual behavior during … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
(47 reference statements)
1
12
0
1
Order By: Relevance
“… 13 In sum, COVID-19 crisis may prompt or decrease different aspects of sexual life, depending on explored variables and diverse determinants, such as gender, privacy, age, or the perception of confinement as unbearable. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“… 13 In sum, COVID-19 crisis may prompt or decrease different aspects of sexual life, depending on explored variables and diverse determinants, such as gender, privacy, age, or the perception of confinement as unbearable. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…In spring 2020, well over 100 countries and billions of people were in lockdown to prevent the spread of the novel coronavirus disease (COVID-19). As fear of contagion and pandemic mitigation measures forced individuals to minimize physical contact (Dunford, 2020 ), technology-mediated communication gained importance in satisfying the need for intimacy (Ballester-Arnal et al, 2020 ). One way to be intimate without physical contact is sexting, i.e., the exchange of sexually suggestive or explicit texts and (semi-)naked photographs via mobile phones and social media (Albury et al, 2013 ; Amundsen, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research showed that during the lockdown, there was a sharp decrease in partnered sexual activity (Li et., 2020 ; Sanchez et al, 2020 ). In particular, those who did not live with a partner reported a decline in their sexual lives during the lockdown (Ballester-Arnal et al, 2020 ) Even within couples (who lived together), fear of contagion and limited opportunities have reduced physical contact (Ibarra et al, 2020 ; Schiavi et al, 2020 ) as an immediate form of stress and fear relief.…”
Section: Introductionmentioning
confidence: 99%
“…referidos a poblaciones de adultos en general (Alvites-Huamani, 2020;González-Sanguino et al, 2020;Hidalgo et al, 2020;Jiménez et al, 2020;Odriozola-González et al, 2020;Rodríguez-Hidalgo et al, 2020;Subirón, 2020;personas mayores (Velasco et al, 2020), niños y adolescentes (Gómez-Becerra et al, 2020;Orgilés et al, 2020;Pedreira, 2020), y en profesionales de la salud (Romero et al, 2020;Monteiro da Silva et al, 2020). También se ha constatado que el confinamiento y la pandemia de COVID-19 puede afectar negativamente a otras facetas psicológicas como la conducta sexual (Ballester-Arnal et al, 2020;, el equilibrio laboral -balance ocupacional-(González-Bernal et al, 2020) y la perturbación de la vida cotidiana (Parada y Zambrano, 2020). Así mismo, se han llevado a cabo estudios de intervención para reducir y/o prevenir el impacto emocional de la pandemia (Jiménez et al, 2020;Lugo-González et al, 2020;Rodríguez-Ceberio, 2020), así como también propuestas de actuación (Espada et al, 2020;Pedreira, 2020).…”
Section: Introductionunclassified